Interoceptive regulation of bone homeostasis: The interplay between the nervous and skeletal systems in pathophysiology - Zeng Xu; Shatong He; Chen Yang; Yang Ye; Genjiang Zheng; Hui Wang; Lei Liang; Chen Xu; Peng Cao; Xiaodong Wu; Bo Hu; Huajiang Chen (Pharmacological Research)
Studies have demonstrated that the nervous system can perceive and respond to signaling from bone tissue, a process termed interoception, which plays a crucial role in the homeostasis of bone tissue. Sensory nerves extensively innervate bone tissue and transmit interoceptive signals to the central nervous system (CNS). The hypothalamus, located within the CNS, is instrumental in processing these interoceptive signals and regulating bone homeostasis through the autonomic nervous system, the release of neuropeptides, and neuroendocrine mechanisms. Although CNS regulation of bone has been recognized for decades, the specific interoceptive mechanisms governing skeletal homeostasis remain an emerging research focus. This review explores the latest advancements in interoceptive regulation of bone homeostasis, highlighting its role in skeletal diseases such as osteoporosis and osteoarthritis(OA). Furthermore, we discuss potential therapeutic strategies targeting interoceptive pathways, including biomaterials, pharmacological interventions, and non-pharmacological approaches. By elucidating the interplay between the nervous and skeletal systems, this review provides new insights into the regulation of bone health and its implications for future treatments of skeletal disorders.